Analysis of the Diversity of Health Status Indices in Sukabumi Regency Using Qualitative Comparative Analysis (QCA) (Jurnal Bina Praja, 2025)
The public health level is a crucial indicator for evaluating the success of health sector development. In Sukabumi Regency, characterized by diverse geography and socio-economic conditions, there are notable variations in the Public Health Degree Index (PHDI) across regions. This study employs Crisp-Set Qualitative Comparative Analysis (csQCA) using Tosmana QCA software to explore the combinations of factors that influence PHDI outcomes. Data were collected from the Sukabumi District Health Office, the Central Statistics Agency, and other secondary sources. The aim is to analyze regional differences in community health and identify the sets of factors that drive high or low PHDI levels. Results show that Clean and Healthy Living Behaviors (CHLB) and sanitation are the most consistent determinants of high PHDI, even in contexts with limited health facilities and budgets. Conversely, improvements in health infrastructure and financial resources are effective only when paired with strengthened CHLB and sanitation practices. Interestingly, extreme poverty does not necessarily hinder achieving a high PHDI if healthy behaviors and environmental sanitation are well-established. On the other hand, areas with low PHDI typically suffer from a combination of unhealthy behaviors and poor sanitation, despite having adequate infrastructure and funding. These insights highlight the need for targeted, area-specific intervention strategies that prioritize enhancing healthy living behaviors and sanitation, along with optimizing health facilities and financial support.
Keywords: Level of Public Health; Sanitation; Regional Intervention